Knowledge management process, knowledge sharing, and teacher literacy skills at vocational high schools - A. Sobandi; Edi Suryadi; M. Arief Ramdhany; Rasto Rasto (Jurnal Cakrawala Pendidikan, 2021)
The development of students in mastering the skills of the 21st century is certainly inseparable from the role of educators in understanding the various skills and the use of digital technology associated with it, supported by knowledge management process and knowledge sharing. The purpose of this study is to analyze the effect of the knowledge management process and knowledge sharing on teacher literacy skills at State Vocational High Schools (VHSs) in West Java.  To collect data, a questionnaire was used. This research used a quantitative approach through descriptive and verification research. Based on the characteristics of the variables, a survey using a 7-point Likert scale questionnaire was conducted.  This research was purposely administered to 162 teachers from 54 VHSs at 27 cities/regencies in West Java. The Partial Least Square Structural Path-Modeling (PLS-PM) was used to test the hypotheses. The research outcomes revealed that the knowledge management processes and knowledge sharing have a positive effect on teacher literacy skills. Information literacy is important for building literacy skills, but achievement is relatively low. The teacher needs to align these skills with more appropriate directions so that teachers’ literacy skills in the learning process can be more effective.